Exercise Intensity Does not Modulate the Effect of Acute Exercise on Learning a Complex Whole-Body Task. (1st February 2020) - Wanner, Philipp; Müller, Theresa; Cristini, Jacopo; Pfeifer, Klaus; Steib, Simon
Highlights: Exercise intensity had no effect on motor skill acquisition or consolidation in a complex whole-body task. Our findings suggest fatigue or interference effects of exercise on motor memory formation. The interaction between exercise and motor memory may depend on motor task complexity. The results emphasize a complex interaction between mechanisms involved in exercise-induced motor memory enhancement. Abstract: High-intensity cardiovascular exercise prior to motor skill practice is postulated to enhance motor memory consolidation (offline learning), whereas moderate-intensity bouts may benefit skill acquisition (online learning). This study aimed at investigating this suggested intensity-dependent effect of exercise in a complex whole-body task. 50 healthy young adults were randomized into one of three groups performing a bout of either (1) high-intense, (2) moderate-intense, or (3) minimal-intense cycling for a total of 17 min immediately prior to skill practice. The motor task required participants to balance on a tiltable platform (stabilometer) for 30 s. During acquisition 15 practice trials were carried out, followed by a retention test 24 h later. Time in balance was calculated for each trial and within- and between-group differences in online (skill improvement during skill acquisition) and offline learning (skill change from last acquisition block to retention) were analyzed. All participants significantly improved balance time during acquisition, with no differences observed between experimental conditions. Similarly, there were no differences in offline learning between groups. Contrary to previous reports, the present data do not support an intensity-dependent effect on motor learning, when exercise is performed prior to task practice. One reason for this might be that similar muscle groups were involved in exercise and the motor task, potentially causing fatigue or interference effects. Further, the results indicate that the memory-promoting effects of acute exercise are task-dependent and may not apply equally for motor skills of different levels of complexity.